Real‐Time Interrogation of Aspirin Reactivity, Biochemistry, and Biodistribution by Hyperpolarized Magnetic Resonance Spectroscopy. Issue 13 (20th February 2019) - Zacharias, Niki M.; Ornelas, Argentina; Lee, Jaehyuk; Hu, Jingzhe; Davis, Jennifer S.; Uddin, Nasir; Pudakalakatti, Shivanand; Menter, David G.; Karam, Jose A.; Wood, Christopher G.; Hawk, Ernest T.; Kopetz, Scott; et al.
Abstract: Hyperpolarized magnetic resonance spectroscopy enables quantitative, non‐radioactive, real‐time measurement of imaging probe biodistribution and metabolism in vivo. Here, we investigate and report on the development and characterization of hyperpolarized acetylsalicylic acid (aspirin) and its use as a nuclear magnetic resonance (NMR) probe. Aspirin derivatives were synthesized with single‐ and double‐ 13 C labels and hyperpolarized by dynamic nuclear polarization with 4.7 % and 3 % polarization, respectively. The longitudinal relaxation constants ( T1 ) for the labeled acetyl and carboxyl carbonyls were approximately 30 seconds, supporting in vivo imaging and spectroscopy applications. In vitro hydrolysis, transacetylation, and albumin binding of hyperpolarized aspirin were readily monitored in real time by 13 C‐NMR spectroscopy. Hyperpolarized, double‐labeled aspirin was well tolerated in mice and could be observed by both 13 C‐MR imaging and 13 C‐NMR spectroscopy in vivo. Abstract : A new trick for an old drug : The successful hyperpolarization of 13 C‐labeled aspirin by DNP is demonstrated. NMR spectroscopy was used to monitor in vitro hydrolysis, transacetylation, and albumin‐binding reactions of hyperpolarized aspirin in real‐time and MRI was employed to visualize its early biodistribution in mice.